Analysis of the need response to the development of the E -module of parabolic motion material at SMA Bengkulu City - Dimas Lingga Iswara; Eko Risdianto; Andik Purwanto (CV Media Inti Teknologi, 2022)
The problem that students often face in their learning is a misunderstanding in studying physics. The reason is because educators only teach physics abstractly through the classroom, without laboratory experiments (practice) or the use of other media aids, such as using ICT-based learning media. The research method used by researchers is research and development (R&D). R&D is a research model for the purpose of producing products and product feasibility tests. This research was conducted through five different stages of the ADDIE development model. Development, implementation and evaluation are not carried out because the purpose of this study is only to develop modules. This module is not directly applicable to classroom learning. The population used in the study was 153 students and 4 physics teachers from 3 high schools in Bengkulu City. The results of the needs analysis are valid and reliable, teachers and students of 3 high schools in Bengkulu City strongly agree with the development of E-modules for parabolic motion materials.